Beneficial effect of low ethanol intake on the cardiovascular system: possible biochemical mechanisms - Sudesh Vasdev; Vicki Gill; Pawan K Singal (Vascular Health and Risk Management, 2006)
Sudesh Vasdev1, Vicki Gill1, Pawan K Singal21Discipline of Medicine, Faculty of Medicine, Memorial University of Newfoundland, St. John’s, Newfoundland and Labrador, Canada; 2Institute of Cardiovascular Sciences, University of Manitoba, Faculty of Medicine, Winnipeg, Manitoba, CanadaAbstract: Low ethanol intake is known to have a beneficial effect on cardiovascular disease. In cardiovascular disease, insulin resistance leads to altered glucose and lipid metabolism resulting in an increased production of aldehydes, including methylglyoxal. Aldehydes react non-enzymatically with sulfhydryl and amino groups of proteins forming advanced glycation end products (AGEs), altering protein structure and function. These alterations cause endothelial dysfunction with increased cytosolic free calcium, peripheral vascular resistance, and blood pressure. AGEs produce atherogenic effects including oxidative stress, platelet adhesion, inflammation, smooth muscle cell proliferation and modification of lipoproteins. Low ethanol intake attenuates hypertension and atherosclerosis but the mechanism of this effect is not clear. Ethanol at low concentrations is metabolized by low Km alcohol dehydrogenase and aldehyde dehydrogenase, both reactions resulting in the production of reduced nicotinamide adenine dinucleotide (NADH). This creates a reductive environment, decreasing oxidative stress and secondary production of aldehydes through lipid peroxidation. NADH may also increase the tissue levels of the antioxidants cysteine and glutathione, which bind aldehydes and stimulate methylglyoxal catabolism. Low ethanol improves insulin resistance, increases high-density lipoprotein and stimulates activity of the antioxidant enzyme, paraoxonase. In conclusion, we suggest that chronic low ethanol intake confers its beneficial effect mainly through its ability to increase antioxidant capacity and lower AGEs.Keywords: low ethanol, hypertension, cardiovascular disease, biochemical mechanisms, advanced glycation end products